Analysis of the Influence of Motivation and Competence on Employee Commitment At XYZ Polytechnic of Jakarta - Caniago, Aspizain; Mardikawaty, Rini; Nurlia, Titim; Sopiah; Bambang Sutrisno, Supadi (ASIAN PUBLISHER, 2023)
This study's title is